2020
DOI: 10.1111/pai.13148
|View full text |Cite
|
Sign up to set email alerts
|

IgE antibody repertoire in nasal secretions of children and adults with seasonal allergic rhinitis: A molecular analysis

Abstract: Background: There is growing interest both in testing IgE in nasal secretions (NS) and in molecular diagnosis of seasonal allergic rhinitis (SAR). Yet, the reliability of nasal IgE detection with the newest molecular assays has never been assessed in a large cohort of pollen allergic patients.Objective: To investigate with microarray technology and compare the repertoires of specific IgE (sIgE) antibodies in NS and sera of a large population of children and adults with SAR.Methods: Nasal secretions were collec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(86 reference statements)
0
11
0
Order By: Relevance
“…The objective of the study published by Sveva Castelli et al was to investigate the repertoires of sIgE antibodies in nasal secretions and sera of children and adults with allergic rhinitis by using microarray technology. 15 IgE antibodies, mostly to airborne allergens, were found in the nasal secretions in 68.3% of the patients, and the authors concluded that they reflect, at population level, the systemic sensitization profiles. However, their data also suggested that sIgE detection in nasal secretions with the biochip used in the study was not sensitive enough to substitute for the serum sIgE measurements.…”
Section: Vincent Ojwangmentioning
confidence: 98%
See 1 more Smart Citation
“…The objective of the study published by Sveva Castelli et al was to investigate the repertoires of sIgE antibodies in nasal secretions and sera of children and adults with allergic rhinitis by using microarray technology. 15 IgE antibodies, mostly to airborne allergens, were found in the nasal secretions in 68.3% of the patients, and the authors concluded that they reflect, at population level, the systemic sensitization profiles. However, their data also suggested that sIgE detection in nasal secretions with the biochip used in the study was not sensitive enough to substitute for the serum sIgE measurements.…”
Section: Vincent Ojwangmentioning
confidence: 98%
“…
The third study presented in this editorial relates to the diagnosis of allergies and more particularly how the measurement of organ‐specific IgE may relate to the disease. The objective of the study published by Sveva Castelli et al was to investigate the repertoires of sIgE antibodies in nasal secretions and sera of children and adults with allergic rhinitis by using microarray technology . IgE antibodies, mostly to airborne allergens, were found in the nasal secretions in 68.3% of the patients, and the authors concluded that they reflect, at population level, the systemic sensitization profiles.…”
mentioning
confidence: 99%
“…Microarrayed allergens can be used for measuring simultaneously IgE reactivity to a large number of different allergen molecules with very small volumes of serum. In this context, it should be mentioned that it has been shown that allergen-specific IgE can be also measured in plasma and other body fluids such as nasal secretions and in milk samples ( 32 35 ). Moreover, it has been shown that dried blood spots on paper can be recovered for specific IgE and IgG measurements which allows sending serum samples as paper dried blood spots in simple envelops without requiring expensive packaging, cooling, and sophisticated transportation ( 36 ).…”
Section: Measurement Of Allergen-specific Ige and Igg Responses With mentioning
confidence: 99%
“…In AR and LAR, sIgE is the principal biomarker that defines the presence of type 2 inflammation. 8 , 9 In AR, sIgE can be detected circulating in the serum or in the mast cells of the skin (systemic atopy), but it can also be found localized in different tissues. 8 , 9 On the other hand, in LAR, sIgE can only be measured in the nasal mucosa (NsIgE).…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 In AR, sIgE can be detected circulating in the serum or in the mast cells of the skin (systemic atopy), but it can also be found localized in different tissues. 8 , 9 On the other hand, in LAR, sIgE can only be measured in the nasal mucosa (NsIgE). Other markers (eg, eosinophils, Th2 cells, and some cytokines) have been proposed, 10 but so far none of them is superior to sIgE in detecting the allergenic trigger that induces the inflammatory response.…”
Section: Introductionmentioning
confidence: 99%